2018
DOI: 10.1177/1179544118781080
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Outcomes in Treatment of Knee Osteoarthritis With 4 Bone Marrow Concentrate Injections

Abstract: Background:Preliminary research suggests that bone marrow concentrate (BMC), which contains mesenchymal stem cells and platelets, is a promising treatment for knee osteoarthritis. The aim of this study was to build on this preliminary research by reporting the short-term progress of 15 patients (20 knees) with knee osteoarthritis through 4 BMC treatments.Methods:Patients underwent four sequential BMC treatments with mean injection times of 13.80 days after the first treatment, 21.40 days after the second treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 31 publications
0
22
0
1
Order By: Relevance
“…However, five studies were excluded being congress abstracts, one study was excluded because it was a case report [25], and one study was excluded because it provided the same data of another included study [26]. Thus, a total of 22 studies were included in the qualitative data synthesis: 4 preclinical studies [27][28][29][30] and 18 clinical studies [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Since the first reports in 2014, the publication trend remarkably increased over time, especially for the clinical studies, with over 50% of the articles published from 2018 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, five studies were excluded being congress abstracts, one study was excluded because it was a case report [25], and one study was excluded because it provided the same data of another included study [26]. Thus, a total of 22 studies were included in the qualitative data synthesis: 4 preclinical studies [27][28][29][30] and 18 clinical studies [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Since the first reports in 2014, the publication trend remarkably increased over time, especially for the clinical studies, with over 50% of the articles published from 2018 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 18 clinical articles found (Table 2), six were retrospective case series, five were retrospective comparative studies, four were randomized controlled trials (RCTs), and three were prospective case series. Eleven studies focused on knee OA [31][32][33][34][35][36][37][38][39][40][41], two focused on hip OA [42,43], two focused on shoulder OA [44,45], while the other three studies described several joints affected by OA [46][47][48]. Intra-articular BMAC injections were performed in 17 studies, while in one study [36], the injection was performed within the tibial and femoral subchondral bone of the knee.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Regarding the therapeutic protocol, five papers dealt with the administration of BMAC alone: two of these involved subchondral BMAC injections [24, 25], whilst in the remaining three, BMAC was injected intra-articularly [1618]. Of these last three papers, one study involved the administration of 4 sequential injections within a 3-month timespan [17]. Other authors administered combined BMAC and PRP within the same session [19, 21, 22] or administered PRP alone after a certain period as a booster injection [20].…”
Section: Resultsmentioning
confidence: 99%
“…In regard to the clinical outcome, the majority of authors employed reliable clinical scores (such as those derived from WOMAC, IKDC, KOOS, or KSS), whereas only a few authors used less known questionnaires, improvement rating scores, or patient satisfaction [17, 2022]. All studies assessed pain through a visual or numerical score such as VAS or NPS, except for two authors [18, 25] who included WOMAC and KSS questionnaires, which have sections on patient pain.…”
Section: Resultsmentioning
confidence: 99%
“…While there is some evidence in the literature of a positive effect of MSCs on KOA [110][111][112][113], there is a lack of level I evidence indicating stem cell therapy for KOA. Furthermore, a recent prospective, placebo-controlled FDA monitored study found that at 6 months follow-up, BMAC injections provided the same amount of improvement in pain and activity as saline [114•].…”
Section: Stem Cellsmentioning
confidence: 99%